2021
DOI: 10.4269/ajtmh.21-0164
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Serology of SARS-CoV-2-Infected Individuals in India: A Prospective Cohort Study

Abstract: Clinical and epidemiological characteristics of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) are now widely available, but there are few data regarding longitudinal serology in large cohorts, particularly those from low-income and middle-income countries. We established an ongoing prospective cohort of 3,840 SARS-CoV-2-positive individuals according to RT-PCR in the Delhi-National Capital Region of India to document clinical and immunological characteristics during illness and convalescence. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…These women were exposed to hyperglycemia in the past, and remain at a high risk of future diabetes, however, they did not meet the criteria for diabetes in the present assessment. Rapid decay of antibody response and lower seroprevalence rates have been reported in patients with mild/asymptomatic infection [ 42 , 43 ]. The seroprevalence data reported in our study could therefore be an underestimate.…”
Section: Discussionmentioning
confidence: 99%
“…These women were exposed to hyperglycemia in the past, and remain at a high risk of future diabetes, however, they did not meet the criteria for diabetes in the present assessment. Rapid decay of antibody response and lower seroprevalence rates have been reported in patients with mild/asymptomatic infection [ 42 , 43 ]. The seroprevalence data reported in our study could therefore be an underestimate.…”
Section: Discussionmentioning
confidence: 99%
“…Although this is lower than other studies, where seroconversion rates have been 84.7% at 10-28 days respectively, these studies followed individuals who had been hospitalised due to COVID19. 17 When hospitalised individuals were stratified by symptom severity, the cumulative percentage of anti-N positive asymptomatic individuals was 60% at 22-28 days. 17 Other studies in hospitalised individuals have also demonstrated symptom severity is associated with an earlier peak in anti-N titres, as well as determining longer duration of anti-N positivity.…”
Section: Discussionmentioning
confidence: 97%
“…17 When hospitalised individuals were stratified by symptom severity, the cumulative percentage of anti-N positive asymptomatic individuals was 60% at 22-28 days. 17 Other studies in hospitalised individuals have also demonstrated symptom severity is associated with an earlier peak in anti-N titres, as well as determining longer duration of anti-N positivity. 22,23 Difference in anti-N over time was seen when the data was disaggregated by sex, with earlier peak and waning in females.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Others and we have shown that antibody levels wane over time. [1][2][3] Antigenic exposure through both vaccination and natural infection may act synergistically to boost immune responses. 4 There is a need for an evidence-driven booster vaccination policy depending on durability of immune response.…”
Section: Conclusion and Relevancementioning
confidence: 99%